2019
DOI: 10.1111/cfs.12698
|View full text |Cite
|
Sign up to set email alerts
|

Parental participation in child protection case conferences

Abstract: Child protection case conferences (CPCCs) are a fundamental part of child protection processes within the United Kingdom. They provide a mechanism for professionals and families to share information, enter an assessment dialogue, and develop a plan for intervention and support. The participation of parents is a core feature of U.K. and Scottish CPCCs. This reflects an international trend that recognizes the rights of family members to participate in the decision‐making processes of child protection. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…The release of those convicted of serious crimes undoubtedly has an impact on those who have been affected by them. However, as we have previously argued, notions of participation are contested and not without problem (Jackson et al, 2020). Perhaps for this reason a review of international responses to victim participation in the context of early release concluded that victim participation remains limited (Braun, 2019b) and there is still no consensus as to how victim rights can be upheld in the context of early release proceedings.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The release of those convicted of serious crimes undoubtedly has an impact on those who have been affected by them. However, as we have previously argued, notions of participation are contested and not without problem (Jackson et al, 2020). Perhaps for this reason a review of international responses to victim participation in the context of early release concluded that victim participation remains limited (Braun, 2019b) and there is still no consensus as to how victim rights can be upheld in the context of early release proceedings.…”
Section: Discussionmentioning
confidence: 80%
“…The concept of participation is not, however, unproblematic. The findings of the study by Jackson, Kelly, and Leslie (2020) raise important questions about the extent to which participants can be considered to meaningfully participate in formal legal processes. In the context of parole, tensions exist between the judicial function of the Parole Board and the informed rights‐based discourses of prisoner participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in finding challenging interpersonal interactions difficult to tolerate because of high levels of affect associated with these exchanges. From a parental perspective, demanding and anxiety-provoking interpersonal interactions describes much of their contact with social workers in child protection systems [46,50]. A scoping review of literature regarding parenting after a history of child maltreatment [51] found that traumatised parenting coping strategies included PTSD fight, flight, and freeze responses to perceived threat, which impacted upon relationships with infants, partners, and professionals.…”
Section: Complex Trauma and Epistemic Trustmentioning
confidence: 99%
“…In accordance with Burnham (2005) and Daniel (2012), clients need to feel that professionals are sensitive to their responses and that there is some freedom to engage in ways that make sense to them in terms of family and cultural values, scripts, style, myths, and so on. Empowerment and participation are key principles of child protection (Arbeiter & Toros, 2017;Fuller & Zhang, 2017;Jackson et al, 2020;Lehtme & Toros, 2020;Platt, 2012;Toros et al, 2018).…”
Section: Systemic Reflexivity In Social Work Practicementioning
confidence: 99%